2015
DOI: 10.1016/j.celrep.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lung Injury Results from Innate Sensing of Viruses by an ER Stress Pathway

Abstract: SUMMARY Incursions of new pathogenic viruses into humans from animal reservoirs are occurring with alarming frequency. The molecular underpinnings of immune recognition, host responses, and pathogenesis in this setting are poorly understood. We studied pandemic influenza viruses to determine the mechanism by which increasing glycosylation during evolution of surface proteins facilitates diminished pathogenicity in adapted viruses. ER stress during infection with poorly glycosylated pandemic strains activated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 56 publications
2
55
1
Order By: Relevance
“…The virulence of these viruses in mice has previously been studied, but only at high infectious dose of 10 6 plaque forming unit (PFU) per mouse1112. At this high virus dose, there was no correlation between H3N2 virulence and receptor binding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The virulence of these viruses in mice has previously been studied, but only at high infectious dose of 10 6 plaque forming unit (PFU) per mouse1112. At this high virus dose, there was no correlation between H3N2 virulence and receptor binding.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that increasing HA glycosylation can reduce H3N2 virulence in mice through virus neutralization by respiratory tract collectin SP-D11 and through abrogation of the inflammation associated with activation of ER stress pathways12. Glycans on HA can also reduce receptor binding91022232635, which in turn may affect viral virulence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively or additionally, the decrease in virulence of glyV G virus in mice despite its full capacity to replicate in the lungs could be explained by an avoidance of endoplasmic reticulum (ER) stress during transport of the HA to the plasma membrane. Indeed, Hrincius et al recently demonstrated that the recognition of poorly glycosylated HA by an ER stress pathway result in acute lung inflammation in mice (Hrincius et al, 2015). Conversely, highly glycosylated HA are not recognized by ER stress, resulting in a decrease of lung inflammation and associated pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TUDCA is implicated as a therapy for hepatitis B virus infection [21]. TUDCA also inhibits IAV replication [22] by suppressing the inositol-requiring enzyme 1 (IRE1) branch of the unfolded protein response (UPR) [22,23], a conserved molecular network orchestrating ER pathology.…”
Section: Introductionmentioning
confidence: 99%